Appraisal System Recognized in President Jokowi’s Speech at the APEC SEO Summit 2014 in Beijing, China - J. Sutomo (Universitas Stikubank (UNISBANK) Semarang, 2016)
This study attempts to construe the Appraisal System of Jokowi’s speech at the APEC CEO Summit on 10 November 2014 in Beijing China. The analysis focused on Engagement, Attitude, and Graduation systems of the speech. The data were analyzed using the Appraisal theory proposed by Martin and White (2005), and the method used is descriptive which provides a detailed profile of an event, condition or situation using either quantitative, qualitative or a combination of methods. The results revealed that the most dominant Appraisal device was Attitude system, and Jokowi positioned himself at the same level as the participants of the APEC conference who were mostly the top leaders in their countries. The readers of the speech text are positioned as the ones who accept Jokowi’s assessment about the infrastructure’s conditions in Indonesia and what he plans to do to improve that conditions.Key words: Appraisal System, Engagement, Attitude, Graduati